Remittances and Return Migration - William Collier; Matloob Piracha; Teresa Randazzo (University of Kent, School of Economics, 2011)
This paper utilises survey data of return migrants to analyse the determinants of remittances sent while the migrants were abroad. We approach our research question from the perspective of three sending countries in the Maghreb, namely Algeria, Morocco and Tunisia. We investigate the remittance behaviour using the migrants' conditions before migration as well as during the migration experience. Using a two-part model, we show that the decision to remit and the amount remitted depend on a combination of different migrant characteristics as well as the duration and form of migration. We also consider if the remittance behaviour is dependent on the type of return: decided or compelled. We show that those who decided to return have a higher probability to remit for investment purposes and remit more as the time spent abroad increases.
Keywords: F22; F24; 330; remittances; return migration; Maghreb countries; Rücküberweisungen; Rückwanderung; Schätzung; Maghreb